Concentrations of oligosaccharides in human milk and child growth - Philipp Menzel; Mandy Vogel; Sean Austin; Norbert Sprenger; Nico Grafe; Cornelia Hilbert; Anne Jurkutat; Wieland Kiess; Aristea Binia (BMC, 2021)
Abstract Background The relationship between human milk oligosaccharides (HMO) and child growth has been investigated only insufficiently with ambiguous results. Therefore, this study examines potential influencing factors of HMO concentrations and how HMO are associated with child growth parameters. Methods Milk samples from the German LIFE Child cohort of healthy children were analyzed for 9 HMO. Putative associations with maternal and child cofactors and child height, head circumference and BMI between 3 months and 7 years of age were examined. Secretor status, defined as the presence of 2'-fucosyllactose, was investigated for associations with infant outcomes. Results Our population consisted of 21 (14.7%) non-secretor and 122 (85.3%) secretor mothers. Maternal age was significantly associated with higher 3'SL concentrations; gestational age was associated with LNT, 6'SL and LNFP-I. Pre-pregnancy BMI was negatively associated with LNnT only in non-secretors. The growth velocity of non-secretors' children was inversely associated with LNnT at 3 months to 1 year (R = 0.95 [0.90, 0.99], p = 0.014), 1 to 2 years (R = 0.80 [0.72, 0.88], p < 0.001) and 5 to 6 years (R = 0.71 [0.57, 0.87], p = 0.002). 2'FL was negatively associated with BMI consistently, reaching statistical significance at 3 months and 4 and 5 years. Children of non-secretors showed higher BMI at 3 months, 6 months, and 3, 6, and 7 years of age. Conclusion We found that some associations between HMO and infant growth may extend beyond the infancy and breastfeeding periods. They highlight the importance of both maternal and infant parameters in the understanding of the underlying associations. Trial registration The study is registered with ClinicalTrial.gov: NCT02550236 .